Auditory Perceptual Learning for Speech Perception Can be Enhanced by Audiovisual Training - Bernstein, Lynne E.; Auer, Edward T.; Jiang, Jintao; Eberhardt, Silvio P. (Frontiers in Neuroscience, 2013)
Speech perception under audiovisual conditions is well known to confer benefits to perception such as increased speed and accuracy. Here, we investigated how audiovisual training might benefit or impede auditory perceptual learning speech degraded by vocoding. In Experiments 1 and 3, participants learned paired associations between vocoded spoken nonsense words and nonsense pictures in a protocol with a fixed number of trials. In Experiment 1, paired-associates (PA) audiovisual (AV) training of one group of participants was compared with audio-only (AO) training of another group. When tested under AO conditions, the AV-trained group was significantly more accurate than the AO-trained group. In addition, pre- and post-training AO forced-choice consonant identification with untrained nonsense words showed that AV-trained participants had learned significantly more than AO participants. The pattern of results pointed to their having learned at the level of the auditory phonetic features of the vocoded stimuli. Experiment 2, a no-training control with testing and re-testing on the AO consonant identification, showed that the controls were as accurate as the AO-trained participants in Experiment 1 but less accurate than the AV-trained participants. In Experiment 3, PA training alternated AV and AO conditions on a list-by-list basis within participants, and training was to criterion (92% correct). PA training with AO stimuli was reliably more effective than training with AV stimuli. We explain these discrepant results in terms of the so-called "reverse hierarchy theory" of perceptual learning and in terms of the diverse multisensory and unisensory processing resources available to speech perception. We propose that early audiovisual speech integration can potentially impede auditory perceptual learning; but visual top-down access to relevant auditory features can promote auditory perceptual learning.